Habermas, modernity, and law - Deflem, Mathieu (Philosophy & social criticism (London, England), 1996)
The work of J[um]urgen Habermas has long been regarded as central to the development of social and political theory and philosophy in the late twentieth century. With the publication of his latest book Between Facts and Norms, Habermas signalled the importance of exploring modern legal theory to our understanding of democratic society.